MENARASIKAN ULANG LABEL KOLEKSI ARCA CAMUNDI DI PUSAT INFORMASI MAJAPAHIT: SEBUAH TINJAUAN BIOGRAFI BENDA - Yusuf, Muhamad Satok (Handep: Jurnal Sejarah dan Budaya, 2024)
This paper discusses the significance of presenting an educational, holistic, and neutral narrative of a museum collection according to the ICOM 2022 definition of a museum. The Camundi statue, one of the iconic collections of the Majapahit Information Center, is an essential example of museum curatorial bias. Visitors are highly interested in the historical journey of the Camundi statue; however, they lack access to a neutral and holistic information label from the collection. This research emphasises the biography of the Camundi statue's journey by examining the dynamics of the statue's role based on its meaning, research history, and preservation. The study applied a descriptive qualitative approach with the basis of historical archaeology and interpretation according to Igor Kopytoff's concept of the biography of things. The findings reveal ongoing debates among experts regarding the statue's identity and historical journey. The Camundi statue has undergone various transformations in its role, from a revered object of worship to a disaster relic, an item of preservation, and finally, a museum exhibit that should be presented without curatorial bias. The critical evaluation in this study recommends the re-narration of the collection label by considering four aspects of holistic, educative, and neutral narratives